Universal Donors and Recipients are Not So Universal! (Pakistan Journal of Kidney Diseases, 2021)
Blood transfusion should only be used when the benefits outweigh the risks and there are no appropriate alternatives. Blood transfusion is considered safe when right blood is given to right patient at right time and right place. Right blood is screened for Transfusion Transmissible Infections and is ABO, Rh compatible.Here we discuss the donor strategies and revist the concept of universla dosnor or recipient.
Keywords: Blood transfusion; universal donor; universal recipient; alloimmunity; Rh neagtive; Rh positive; compatibility